Chikungunya virus seroprevalence in asymptomatic blood donors during an outbreak in the Federal District of Brazil. Issue 4 (27th April 2022) - da Silva Mendes, Ana Micaelle; Cilião‐Alves, Daiani Cristina; Pimentel, Bárbara Maciel Sidou; Slavov, Svetoslav Nanev; de Araújo, Wildo Navegantes; Haddad, Rodrigo
Abstract: Introduction: Chikungunya virus (CHIKV) is a mosquito‐borne alphavirus belonging to the Togaviridae family. The symptomatic infection is characterised by acute febrile disease which generally results in severe arthralgia and myalgia, however, most of the CHIKV infections remain asymptomatic. CHIKV RNA detection in asymptomatic volunteers may be responsible for the transfusion transmission of this infection, especially during outbreaks. There is no information for CHIKV seroprevalence among blood donors from the Federal District of Brazil. Aim: In early 2019, the Federal District of Brazil experienced a CHIKV outbreak, and this study evaluates the anti‐CHIKV IgM and IgG presence in a well characterised cohort of blood donors from this region. Methodology: Blood samples were collected from 450 volunteer blood donors during a CHIKV outbreak and tested for the presence of anti‐CHIKV IgG and IgM antibodies using ELISA. Results: The CHIKV seroprevalence was 0.89% ( n = 4/450) and anti‐CHIKV IgM prevalence was 1.11% ( n = 5/450). Conclusion: The obtained results demonstrated that at least some of the blood donors have experienced CHIKV infection which can be related to a hypothetical risk of CHIKV transfusion transmission. More studies are necessary in order to examine the impact of CHIKV on blood transfusion.